Assessment of Gastrointestinal Symptoms in Patients with Type 2 Diabetes Mellitus: A Cross-Sectional Study - Al Abdulqader, Abdulrhman Khaled; Albadrani, Ahmed Abdullah; Al Mogairen, Saleh Khalid; Alsharidah, Aeshah Salem; Alqahtani, Wafa Yahya; Buzaid, Reem Khalid (Journal of Neonatal Surgery, 2025)
Background: Gastrointestinal (GI) symptoms are common but often underrecognized complications of type 2 diabetes mellitus (T2DM), contributing to poor quality of life and suboptimal glycemic control. Aim: To assess the prevalence, severity, and predictors of GI symptoms among patients with T2DM attending outpatient clinics. Methods: A cross-sectional study was conducted among 548 adults with T2DM at the polyclinics of King Faisal University, Saudi Arabia. Data on demographics, clinical profiles, and GI symptoms were collected using structured interviews and the validated Gastrointestinal Symptom Rating Scale (GSRS). Logistic regression was used to identify independent predictors of moderate-to-severe symptoms. Results: The overall prevalence of ≥1 moderate-to-severe GI symptom was 75.2%, with indigestion (46.7%), reflux (38.9%), and constipation (37.8%) being most common. Nearly 49% had moderate and 26.5% had severe symptom scores. Female gender (OR=1.42, p=.006), diabetes duration ≥10 years (OR=1.37, p=.034), HbA1c ≥9% (OR=1.58, p=.001), BMI ≥35 kg/m² (OR=1.41, p=.028), and metformin-only therapy (OR=1.26, p=.043) were significantly associated with higher symptom burden. Conclusion: GI symptoms are highly prevalent among patients with T2DM and are linked to multiple modifiable clinical factors. Routine screening and individualized interventions are essential to enhance symptom control and optimize overall diabetes management.